Critical thinking as learning and innovation skill in the 21st century - Dina Merris Maya Sari; Aulia Kusuma Wardhani (Universitas Sarjanawiyata Tamansiswa, 2020)
The essential element of encouraging national competitiveness in the revolutionary industry 4.0 is to prepare a more innovative learning system and to enhance the competence of graduates with 21st-century skills (Learning and Innovations Skills). There are 4Cs (Critical thinking, Creativity, Collaboration, and Communication) that can be implemented. Critical thinking is about problem-solving skills. The aim of this research is to determine the correlation of critical reading skills with critical thinking skills on 28 EFL students. The technique used to analyze the data is the correlation analysis using r Product Moment formula. The results showed a positive correlation between critical reading skills and critical thinking skills. Thus, it can be concluded that there is a correlation between critical reading strategy with critical thinking skills. To make this research better, the researcher suggests the next researcher to conduct such research by using experimental research which provides a strategy to improve students’ critical thinking.